2012
DOI: 10.1590/s1806-00132012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de dor e do perfil epidemiológico, de pacientes atendidos no pronto-socorro de um hospital universitário

Abstract: Pain and epidemiologic evaluation of patients seen by the first aid unit of a teaching hospital* Avaliação de dor e do perfil epidemiológico, de pacientes atendidos no pronto-socorro de um hospital universitário

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
1
9
0
7
Order By: Relevance
“…Esses achados podem refletir os resultados negativos de estudos que apontaram que a dor, seja ela aguda ou crônica, é subdiagnosticada, mal avaliada, subtratada, com baixa resolutividade e por vezes negligenciada em vários níveis de atenção à saúde [4][5][6] .…”
Section: Introductionunclassified
“…Esses achados podem refletir os resultados negativos de estudos que apontaram que a dor, seja ela aguda ou crônica, é subdiagnosticada, mal avaliada, subtratada, com baixa resolutividade e por vezes negligenciada em vários níveis de atenção à saúde [4][5][6] .…”
Section: Introductionunclassified
“…Nevertheless, it is observed that studies on this topic are still scarce, especially when it comes to epidemiological studies and their social determinants [10][11][12]. In this perspective, the knowledge of factors about the development of oral health diseases for various populations is imperative, including individuals with specific health conditions such as the case of patients with hereditary bleeding disorders by factor deficiency (HBD).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high prevalence worldwide, pain is currently considered the fifth vital sign and requires from health professionals specific skills and knowledge for its evaluation and management. However, the difficulty of teams to perceive its extension is still a critical point for its control 8 . The lack of specific knowledge of professionals about pain evaluation methods/scales, the unawareness of the implementation of the fifth vital sign and, consequently, the inadequacy of pain handling may contribute to unnecessary suffering and decreased QL of acute and chronic pain patients 9 .…”
Section: Introductionmentioning
confidence: 99%